Food and feeding habits of Juvenile white sea bass, Lates Calcarifer (Bloch) from the Shibsha river in the South-Western coastal region of Bangladesh - Kamruzzaman, Sk; Al Noor, Syeda Mushahida; Hossain, Md Delwer (Journal of Bio-Science, 2015)
Abstract not available DOI: http://dx.doi.org/10.3329/jbs.v21i0.22528 J. bio-sci. 21: 141-144, 2013